Modelling hydro-morpho dynamics of river junctions under the impact of unsubmerged vanes - Ali, Hydar Lafta (2019)
Controlling the flow and river bed morphology in the confluence and branching junctions are important in rivers training and navigation works. The flow in a river junction is highly complex, due to rapid changes associated with flow dynamics, sediment transport, and geomorphology. Erosion and deposition zones are considered as the main critical features that appear at the river junction and causing many problems such as increasing the possibility of flood risks at the river confluence, on the other hand, a shortcoming of the inflow discharge at the river branching which effects different water supply projects. In this study, two cases have been selected owing to their suffering from hydro-morpho dynamics issues. The first case is a confluence of Kurau and Ara rivers located at tropical region Perak, Malaysia, while the second case is a branching of Tigris river located at temperate region Missan, Iraq. The aim of this study is to control the hydro-morpho dynamics features at the junction of a confluence and branching rivers. Measured and acquired data were used to investigate the scour hole that usually formed in the erosion zone and bar formed in the deposition zone. The data of the confluence junction was acquired while for the branching junction was measured. Garmin echoMap 50s device was used to measure the bathymetry survey, while Son Tek River Surveyor device M9 was used to collect discharge, velocity distribution, and cross-section geometry. In addition, Van Veen Grab sampler was used to collect bed material sampling of the Tigris branching junction. The results of data collection for the confluence of Kurau and Ara rivers show that the velocity was ranged between 0.8 and 1.1 m/s at the location of the maximum scour zone and between 0.1 and 0.3 m/s at the location of deposition zone, while for the branching of the Tigris river the velocity was around 0.5 m/s at the location of the scour zone and 0.1 m/s at the deposition zone. A 2D numerical model of Mflow_02 solver was used to build, calibrate and validate the numerical models using field data to simulate the selected river junctions before simulating various arrangements of unsubmerged vanes as control structures. This solver was able to calculate two-dimensional plane unsteady flow, river bed morphology and sediment transport by unstructured meshes of finite element method. The error of the model output was found to be less than 20% in both cases. The simulations with different arrangements of unsubmerged vanes were proposed as control structures to mitigate scouring and deposition zones that usually occurred at natural river junctions. The results revealed that the most effective size and location of unsubmerged vanes mainly depend on their performance in deposition and scouring zones. For both cases, simulation results show that a single unsubmerged vane can successfully control the scouring and deposition zones. In the confluence junction, the third scenario of installing a single unsubmerged vane with 10 m length at an angle of 30° gave the best solution for diminishing the maximum scour zone and minimizing the deposition zone. In branching junction, the results of the fourth scenario by introducing a single unsubmerged vane with 50 m length, placed perpendicular to the flow direction of the main branching river, show that the deposition zone was reduced to 82% when compared with the simulation without vane. In summary, this study addresses the applicability of using the 2D numerical model in complex riverine system for predicting hydro-morpho-dynamics changes in junctions with and without vanes as training structures. The significance of this study is attributed to the simulation of various scenarios for controlling scour and deposition zones by using unsubmerged vanes and recommended the best solution that provides minimum scouring and deposition zones and thus may enhance river flow dynamics.